2022
DOI: 10.3390/ijerph191811374
|View full text |Cite
|
Sign up to set email alerts
|

Source Identification and Superposition Effect of Heavy Metals (HMs) in Agricultural Soils at a High Geological Background Area of Karst: A Case Study in a Typical Watershed

Abstract: Exogenous sources and the superposition effect of HMs in agricultural soils made the idenfication of sources complicated in a karst area. Here, a typical watershed, a research unit of the karst area, was chosen as the study area. The smaller-scale study of watersheds allowed us to obtain more precise results and to guide local pollution control. In this study, sources of HMs in agricultural soil were traced by a CMB model. Superposition effects were studied by spatial analysis of HMs and enrichment factor (EF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The adsorption sites on the soil surface are progressively saturated. 42 It was found that the electron effect of Cd, Pb, and Zn in the surface soil was significantly higher than that in the subsoil and increased with depth. Therefore, it is not difficult to see that the content of organic matter causes the difference of heavy metal adsorption in each layer of soil.…”
Section: The Heterogeneity Of Soilmentioning
confidence: 95%
“…The adsorption sites on the soil surface are progressively saturated. 42 It was found that the electron effect of Cd, Pb, and Zn in the surface soil was significantly higher than that in the subsoil and increased with depth. Therefore, it is not difficult to see that the content of organic matter causes the difference of heavy metal adsorption in each layer of soil.…”
Section: The Heterogeneity Of Soilmentioning
confidence: 95%
“…At the same time, the soil seriously polluted by heavy metals may become a long-term pollution source of groundwater and ecosystem ( Konyshev et al, 2020 ; Li et al, 2009 ). Therefore, heavy metal pollution in soil is becoming an increasingly serious environmental problem ( Zhong et al, 2018 ; Yang, Wu & Yang, 2022 ; Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the status of soil heavy metals pollution in karst areas in different land and vegetation cover types appeared in karst areas ( Han et al, 2022 ; Liu et al, 2022 ; Sun et al, 2020 ). Such as natural background, agricultural activity area ( Zhang et al, 2021 ; Han et al, 2012 ; Zeng et al, 2019 ), mining area ( Zhou et al, 2022 ; Zhang et al, 2022 ; Wang et al, 2022b ; Qi et al, 2022 ) has become a major thrust of research. The research content is mainly based on the distribution characteristics of soil heavy metal content or how to reduce the heavy metal content in soil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly serious cadmium (Cd) pollution has been caused by industrialization and technological development with large amounts of waste released [1][2][3]. Heavy metals can cause non-biodegradable bioaccumulation and have remarkable toxicity to organisms, leading to severe damage to biology and ecosystems in low concentrations [4][5][6]. For example, cadmium (Cd) can accumulate in the food chain and be a cause of great public concern, such as the Cd-related disease (Itai-Itai disease) in Japan [7,8].…”
Section: Introductionmentioning
confidence: 99%